Pharmaceutical and Biotechnological Potential of Acorus Calamus Linn.: An Indigenous Highly Valued Medicinal Plant Species - Mittal, Neha; Ginwal, H. S.; Varshney, V. K. (Pharmacognosy Reviews)
Acorus calamus Linn. is an highly valued herbal medicinal plant in India and other European countries. From very early times it is used as an ingredient of several drugs of the Unani, Ayurveda and Local Health Care Systems. The rhizome, roots and leaves of this plant have been used from ancient times in India for the treatment of a variety of ailments and as a repellent and toxicant. The rhizome contains active ingredients possessing insecticidal, antifungal, antibacterial and allelopathic properties. The extract of A. calamus rhizome is used in the formulations of many general tonics. In India, the powdered rootstock and rhizome are used as an antispasmodic, anthelmentic and insecticide. The fragrant oil obtained from the rhizome is also used as flavorings in alcoholic beverages and as fragrant essences in perfumes and sacred oils. The major disadvantage of this oil is the presence of high quantity of carcinogenic β-Asarone compound, due to which this species is not being optimally used in India. The essential oil obtained from this species was found to be very effective against some pathogenic and non-pathogenic fungi (shows strong antifungal activity) and towards the gram negative as well as gram-positive bacteria in vitro. The multifarious properties of A.calamus make it as a potential plant species for various industrial applications. The present review described the applications of A.calamus in various pharmaceutical and biotechnology-based industries.
Keywords: Acorus calamus; β-Asarone; Carcinogenic; Essential oil; Rhizome